Legal Protection for Children Whose Parents Are Online Gambling and Drug Addicts: Maqāṣid Sharī‘a Perspective - Sahrul, Muhammad Rifky Akbar; Kara, Siti Aisyah; Ilyas, Musyfikah (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
Legal protection for children is a measure of national civilization, therefore it is mandatory to be attempted according to the capabilities of the nation and state. Because child protection is a legal action that has legal consequences. As educators, parents are responsible for creating a nurturing environment that can provide a sense of security and comfort to children. Based on this responsibility, parents must be good role models for their own children, but this responsibility cannot be fulfilled if parents become thieves and carry out actions that are reproachful, one of which is being involved in drugs and online gambling that occurs in Rade Village. This study aims to describe the condition of parents as drug and online gambling addicts with a phenomenological approach and case studies, data is collected through in-depth interviews with informants. The results of this study indicate that there are no laws and regulations governing the protection of children from parents who are addicted to drugs and online gambling. Parents who are addicted to drugs and online gambling have an impact on children, both in terms of economy, family, children’s education, and even children’s health, both in terms of children’s psychology and physical health. In the maqasyid syaroah, the protection of children from parents who are addicted to drugs and online gambling is included in al daruriyat al khams which includes maintaining religion (hifz ad din), maintaining the soul (hifz an nafs), maintaining family and descendants (hifz an nasabu wal ar raddu), maintaining reason (hifz al aql), and maintaining property (hifz al mal). This category of ad daruriyah al-khams is something that must not be absent (must exist) for the sake of upholding goodness and welfare, both concerning hereafter and worldly affairs. If this aspect does not exist, then it cannot be realized, namely worldly life (chaos) and a life in the hereafter that is suffering and miserable. Legal protection efforts that can be given to children whose parents are addicted to drugs and online gambling are in the form of assistance and determining the child’s custody rights so that they do not fall into the hands of irresponsible parents.